Editorial: 2022 Retrospective: structural materials - L. Provis, John; Putra Jaya, Ramadhansyah; Napoli, Annalisa; Kanellopoulos, Antonios (Frontiers Media SA, 2024)
Welcome to the Research Topic “2022 Retrospective: Structural Materials.” This curated Research Topic highlights esteemed spontaneous articles from the past few years, personally selected by our Chief Editor, Prof. John L. Provis. The work showcased here underscores the extensive spectrum of research conducted within the section and seeks to illuminate its primary areas of interest. All the studies presented here demonstrate significant advancements in theory, experimentation, and methodology, offering solutions to compelling problems. Therefore, the editorial team deems it crucial to give special attention to these matters.